The Relationship between Thyrotropin Receptor Antibody Levels and Intrathyroid Vascularity in Patients with Graves’ Disease - Shih, S.-R.; Chang, J.-S.; Lin, L.-C.; Chang, Y.-C.; Li, H.-Y.; Lee, C.-Y.; Chen, C.-M.; Chang, T.-C. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Thyroid stimulating hormone receptor antibodies (TSHRAbs) are specific autoantibodies of Graves’ disease (GD). They activate adenylate cyclase, induce thyroid growth, and cause an increased rate of thyroid hormone production and secretion. TSHRAbs levels are decreased by treatment and may predict recurrence when they persist. Theoretically, TSHRAbs levels should be related to intrathyroid vascularity (ITV) due to the autoimmunity and inflammation. We aimed to analyze the relationship between TSHRAbs represented by thyrotropin-binding inhibitory immunoglobulin (TBII) levels and ITV measured by thyroid duplex sonography (TDS).56 GD patients were prospectively recruited.ITV, measured using TDS, was defined as follows: (average color-flow area in the right and left sides of the thyroid/total thyroid area in transverse view)×100.The average TBII level was 47.1% and average ITV was 27.24. ITV positively and significantly correlated with TBII (p<0.001).TSHRAbs show significant correlation with ITV. This may help doctors to estimate thyroid autoimmune activity when they performing sonography at clinics.
Keywords: Graves’ disease; thyrotropin receptor antibody; doppler sonography; infrared thermal imaging